2000
DOI: 10.1152/ajpgi.2000.279.5.g1080
|View full text |Cite
|
Sign up to set email alerts
|

A duodenum-specific enhancer regulates expression along three axes in the small intestine

Abstract: Adenosine deaminase (ADA) is expressed at high levels in the epithelium of proximal small intestine. Transgenic mice were used to characterize the regulatory region governing this activation. A duodenum-specific enhancer is located in intron 2 of the human ADA gene at the central site among a cluster of seven DNase I-hypersensitive sites present in duodenal DNA. Flanking DNA, including the remaining hypersensitive sites, is required for consistent high-level enhancer function. The enhancer activates expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
65
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(69 citation statements)
references
References 56 publications
4
65
0
Order By: Relevance
“…Brickner et al (1999) examined homology in noncoding regulatory regions of the human and murine ADA genes and correlated regions of homology with critical ADA T-cell regulatory regions in the first intron of the human ADA gene (Aronow et al 1989(Aronow et al , 1992. Recently, it has been shown that there are additional regions within the first and second introns of the human ADA gene that separately facilitate T-cell enhancer activation (Aronow et al 1995) and control GI expression with both a duodenal enhancer and spatio-temporal modifiers of GI expression (Dusing et al 2000).…”
Section: Adamentioning
confidence: 99%
“…Brickner et al (1999) examined homology in noncoding regulatory regions of the human and murine ADA genes and correlated regions of homology with critical ADA T-cell regulatory regions in the first intron of the human ADA gene (Aronow et al 1989(Aronow et al , 1992. Recently, it has been shown that there are additional regions within the first and second introns of the human ADA gene that separately facilitate T-cell enhancer activation (Aronow et al 1995) and control GI expression with both a duodenal enhancer and spatio-temporal modifiers of GI expression (Dusing et al 2000).…”
Section: Adamentioning
confidence: 99%
“…Extensive studies (3,4,17,19,33,40) on their promoters have identified several transcription factors important for intestinal expression of these genes [cdx-2, hepatocyte nuclear factor (HNF)-1, and GATA family members]. However, intestinal expression of villin and adenosine deaminase depends on enhancer elements in introns 1 and 2, respectively (16,37). Thus the study of other differentiationassociated genes in intestine will provide new insight into the programming essential for development of a functional absorptive surface.…”
mentioning
confidence: 99%
“…It is expressed in all mammalian tissues, but the expression levels vary over a range of several thousandfold and undergo significant changes in various tissues and cell types in a developmentally specific manner (6). A number of distinct genomic regions (regulatory modules) that control ADA tissue expression in mice and humans have been identified and characterized (2,9,15,50,57,60). These modules contain tissue-specific enhancers that bind a variety of transcription factors, which collaborate to control chromatin structure and activate ADA gene transcription in distinct cell types.…”
mentioning
confidence: 99%
“…Gene ablation studies have shown that ADA expression is essential for duodenal integrity and viability (37,59). Transgenic mouse studies have been used to identify and map an enhancer that activates high-level ADA expression specifically in the duodenum (15)(16)(17). The enhancer can activate expression that recapitulates endogenous gene activation exactly along three distinct axes: the cephalocaudal [anterior/posterior (A/P) axis], the crypt-villus differentiation axis, and the axis of developmental time (15,16).…”
mentioning
confidence: 99%